Proposed Filipino Tech-Based Language Competencies: Input to Realigning Filipino Subjects to the Laboratory Junior High School’s Mandate as a Technological Institution - Aira F. Mitra; Melvin O. Mortera (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study produced a set of tech-based Filipino language competencies specially designed for Junior High School students of the Laboratory School. It serves as an initial step toward aligning the Filipino subject with the school’s mandate as a technological institution. The research focused on identifying target competencies for Grades 7 to 10, exploring challenges in implementing a technology-enhanced language curriculum, and crafting competencies that address instructional gaps. The teachers from the Filipino Department, being the direct implementers of the curriculum, were selected as the primary respondents. Their insights were critical in contextualizing the realities of classroom instruction and the integration of technology in language learning. To further strengthen the output, experts in instructional technology and Filipino language education were consulted. The development of the proposed competencies was also guided by the recalibrated K to 12 curriculum, particularly the MATATAG framework. Emphasis was placed on enhancing students' ability to develop, present, and engage with written, visual, and multimodal texts using available digital tools. These competencies are intended to be a relevant and practical contribution to curriculum revision efforts in the Filipino subject area, ensuring that the subject evolves in response to technological advancements and the shifting needs of 21st-century learners. By bridging curriculum goals and technological integration, this study aims to equip Filipino students with the sustainable skills needed for meaningful communication and lifelong learning in a digitally driven world.